Back Trajectory Analysis and Measurement of Ozone in Air Masses Over Lake Michigan - Kuettner, Lindsey (My University, 2014)
The non-attainment status of federal ozone standards in the region surrounding Lake Michigan demonstrates the efficient ozone production in urban and off-shore air masses. The measurement of ozone in air masses over Lake Michigan have been conducted from 2008-2010 via routine ferry routes from Milwaukee, WI, to Muskegon, MI, which is the most exhaustive data set of off-shore observations at the lake level where exposure is most likely. The measurement of ozone, sulfur dioxide, and nitrogen dioxide levels of shoreline Lake Michigan had been conducted in 2009 via Differential Optical Absorption Spectroscopy (DOAS) in Kenosha, WI. The purpose of this study was to report on a series of HYSPLIT back trajectory models showing the dispersion of pollutants from those transects, which were compared to the observational data in an effort to show a correlation between high ozone and the lake-breeze meteorological effects on trace gases ozone and nitrogen dioxide.
Color poster with text, charts, maps, and graphs.
Keywords: Nitrogen dioxide; Ozone--Measurement of; Lake Michigan; HYSPLIT back trajectory model; Posters